HIV testing experiences and their implications for patient engagement with HIV care and treatment on the eve of 'test and treat': findings from a multicountry qualitative study. (23rd July 2017) - Wringe, Alison; Moshabela, Mosa; Nyamukapa, Constance; Bukenya, Dominic; Ondenge, Ken; Ddaaki, William; Wamoyi, Joyce; Seeley, Janet; Church, Kathryn; Zaba, Basia; Hosegood, Victoria; Bonnington, Oliver; et al.
Abstract : Objective: In view of expanding 'test and treat' initiatives, we sought to elicit how the experience of HIV testing influenced subsequent engagement in HIV care among people diagnosed with HIV. Methods: As part of a multisite qualitative study, we conducted in-depth interviews in Uganda, South Africa, Tanzania, Kenya, Malawi and Zimbabwe with 5–10 health workers and 28–59 people living with HIV, per country. Topic guides covered patient and provider experiences of HIV testing and treatment services. Themes were derived through deductive and inductive coding. Results: Various practices and techniques were employed by health workers to increase HIV testing uptake in line with national policies, some of which affected patients' subsequent engagement with HIV services. Provider-initiated testing was generally appreciated, but rarely considered voluntary, with instances of coercion and testing without consent, which could lead to disengagement from care. Conflicting rationalities for HIV testing between health workers and their clients caused tensions that undermined engagement in HIV care among people living with HIV. Although many health workers helped clients to accept their diagnosis and engage in care, some delivered static, morally charged messages regarding sexual behaviours and expectations of clinic use which discouraged future care seeking. Repeat testing was commonly reported, reflecting patients' doubts over the accuracy of prior results and beliefs that antiretroviral therapy may cure HIV. Repeat testing provided an opportunity to develop familiarity with clinical procedures, address concerns about HIV services and build trust with health workers. Conclusion: The principles of consent and confidentiality that should underlie HIV testing and counselling practices may be modified or omitted by health workers to achieve perceived public health benefits and policy expectations. While such actions can increase HIV testing rates, they may also jeopardise efforts to connect people diagnosed with HIV to long-term care, and undermine the potential of test and treat interventions.